(3GdbGfhf GdeSYhOis - (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s ((3CHh jYdi eMeO Hf GdMSjf Hf aGJc GdbGTGfi s)
(3ChdgG (B:s
(3GdeSYhO ef SYO HGddg YR hLd Ke cfJ eJYdbkG HWQa ef CWQGa GdYde GdQjGVi aCKQJ NOeI NRGfJg GdeYehQI GdehSheI GdMceI HbGfhf dUfGYI GdJfLje s
(3BNQgG (B:s
(3hMjf bSe Ydi eG Hjf ehVYjg eG Hjf GdhbJjf aShi dPdc HjfgeG JeJ GdebGdGJ ef GdbGfhf GdeSYhOi MSH eG hLOfG HMeO Gddg hefg s
(3ai GdeYgO fSN CNQi HQbe (B151 - 154 (3adcs
(3Cda GdeDda gPG GdcJGH deSYhO Hf eMehO Hf SHcJcjf SfI (B421s
(3HChdgG JedcGJ YOI efgG Jedc eMeO Hf CMeO NWjH OGQjG heMeO Hf eMeO GdJjRjfi s
(3HgG cKjQ ef GdLOGhd hGdQShe GdgfOSjI s
(3cJHJ Hbde eged GdfbW CMGjfGs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs